A New Hitherto Unreported Histopathologic Manifestation of Mammary Analogue Secretory Carcinoma: "Masked MASC" Associated With Low-grade Mucinous Adenocarcinoma and Low-grade In Situ Carcinoma Components. Issue 9 (October 2016) - Petersson, Fredrik; Michal, Michael; Kazakov, Dmitry V.; Grossmann, Petr; Michal, Michal
Abstract : We present a salivary gland tumor of the parotid gland in a 54-year-old woman, which contained a minor mammary analogue secretory carcinoma (MASC) component (20%) intermixed with a morphologically entirely different mucinous adenocarcinomatous component that comprised 80% of the tumor mass and a morphologically nondescript low-grade intraductal carcinoma (in situ) component. On fluorescence in situ hybridization, a break in the ETV6 gene was documented in the mucinous adenocarcinomatous, the conventional MASC, and the intraductal (in situ) components. RT-PCR failed to reveal an ETV6 - NTRK3 fusion. The entire conventional MASC and only rare mucinous adenocarcinoma tumor cells were mammaglobin positive, whereas the low-grade intraductal carcinoma (in-situ) component was negative. S-100 protein stained only the MASC component.